Dominance and complexity of Begomovirus Species infection on eggplant in lowlands and highlands - Wahyuni, Ratih; Murti, Rudi Hari; Hartono, Sedyo; Nuringtyas , Tri Rini; wijanarko, Arman; Mulyantoro; Nahampun , Hartinio Natalia; Afifuddin, Ahmad; Sari, Shinta Tiara (Comunicata Scientiae, 2026)
Eggplant (Solanum melongena L.) is an important Indonesian crop increasingly threatened by begomoviruses that reduce yield and quality. Transmitted persistently by the whitefly Bemisia tabaci, these viruses are genetically diverse and often occur in mixed infections, intensifying disease severity and complicating control. This study aimed to identify begomovirus species infecting eggplant, determine their geographic distribution and dominance, and characterize the associated B. tabaci biotypes across major eggplant-producing regions of Java, Indonesia. Field surveys were conducted in five provinces—Banten, West Java, Central Java, Yogyakarta, and East Java—covering 30 lowland and 15 highland sites. From each site, 20 symptomatic plants were collected for molecular analysis, while disease incidence (DI) and severity (DS) were assessed from 200 plants. Across 45 sites, mean DI and DS reached 54.0% and 32.7% in lowlands and 34.8% and 26.8% in highlands, respectively. PCR amplification and sequencing confirmed three begomovirus species: Tomato yellow leaf curl Kanchanaburi virus (TYLCKaV), Pepper yellow leaf curl Indonesia virus (PepYLCIV), and Tomato leaf curl New Delhi virus (ToLCNDV). TYLCKaV was the most prevalent, occurring alone or in combination with PepYLCIV, particularly in lowlands, while ToLCNDV occurred at low frequencies, mainly in mixed infections. Four B. tabaci biotypes (A, B, Q, and AN) were detected, with biotype A dominating in lowlands and Q prevailing in highlands. This study provides the first island-wide molecular mapping of begomovirus species and B. tabaci biotypes infecting eggplant in Indonesia and elucidates the complex virus–vector interactions that shape eggplant disease epidemiology in tropical Asia.